NATO-Russia relations after the Newport summit: Reassurance, cooperation and security guarantees - Margarete Klein; Markus Kaim (Stiftung Wissenschaft und Politik (SWP), 2014)
A key aspect of the NATO summit in Newport (Wales) was the reaction of the alliance to Russia's annexation of Crimea and its destabilisation of Eastern Ukraine. However, apart from the decision to create a high-readiness force, and an action plan for Eastern Europe, heads of state and government did not focus enough on the long-term prospects for NATO's relationship with Russia. (SWP Comments)
Keywords: 320